Involvement of ethylene and lipid signalling in cadmium-induced programmed cell death in tomato suspension cells - Yakimova, E T (Plant physiology and biochemistry : PPB, 2006)
Cadmium-induced cell death was studied in suspension-cultured tomato (Lycopersicon esculentum Mill.) cells (line MsK8) treated with CdSO(4). Within 24 h, cadmium treatment induced cell death in a concentration-dependent manner. Cell cultures showed recovery after 2-3 days which indicates the existence of an adaptation mechanism. Cadmium-induced cell death was alleviated by the addition of sub muM concentrations of peptide inhibitors specific to human caspases indicating that cell death proceeds through a mechanism with similarities to animal programmed cell death (PCD, apoptosis). Cadmium-induced cell death was accompanied by an increased production of hydrogen peroxide (H(2)O(2)) and simultaneous addition of antioxidants greatly reduced cell death. Inhibitors of phospholipase C (PLC) and phospholipase D (PLD) signalling pathway intermediates reduced cadmium-induced cell death. Treatment with the G-protein activator mastoparan and a cell permeable analogue of the lipid signal second messenger phosphatidic acid (PA) induced cell death. Ethylene, while not inducing cell death when applied alone, stimulated cadmium-induced cell death. Application of the ethylene biosynthesis inhibitor aminoethoxy vinylglycine (AVG) reduced cadmium-induced cell death, and this effect was alleviated by simultaneous treatment with ethylene. Together the results show that cadmium induces PCD exhibiting apoptotic-like features. The cell death process requires increased H(2)O(2) production and activation of PLC, PLD and ethylene signalling pathways